Association between satellite-detected tropospheric nitrogen dioxide and acute respiratory infections in children under age five in Senegal: spatio-temporal analysis - Ayako Kawano; Yoonhee Kim; Michelle Meas; Karen Sokal-Gutierrez (BMC, 2022)
Highlights Using the satellite-detected tropospheric NO2 concentrations, we observed an association between individual exposure to NO2 and symptoms of Acute Respiratory Infections (ARIs) among children under 5 years old in Senegal. This is the first population-based epidemiological study conducted in Senegal that investigated the adverse health effect of early childhood exposure to ambient concentrations of NO2 on ARIs in children.